Features and behaviours associated with meat consumption in Brazilian university students - Triches, Rozane Marcia; Eickhoff, Verlaine Petri; Candido, Hyrana Gabriela Lucas Guadagnini (Sustainability in Debate, 2024)
We sought to analyse meat consumption and its association with a set of sociodemographic and behavioural variables among university students at the Federal University of the Southern Border/ Brazil. Eight hundred and fifteen university students answered a structured questionnaire and statistical correlation and logistic regression analyses were carried out. Meat consumption is associated (p<0.05) with gender, religion, undergraduate course, income, race, self-control, pro-environmental behaviours and issues related to the meat industry. Regarding adherence and maintenance of a reduced meat consumption pattern, there was a positive correlation with greater ease in preparing food and eating out, motivations linked to the environment, animal causes and the meat industry. Antecedent and consequent behavioural factors are key points for dietary changes in favour of sustainability.